Estudo de métodos físico-químicos e biológico para caracterização e avaliação do anticorpo monoclonal recombinante denosumabe - Dumoncel, Rafaela Ferreira Perobelli (2021)
Denosumab (DmAb) is monoclonal antibody (mAb) that inhibits proliferation and activity of osteoclasts cells, that is commercially available in Brazil as Prolia® and Xgeva®, for treatment of bone diseases. Structurally, it is composed of two heavy chains and two light chains, having a molecular mass of 147 kDa. Fragment crystallizable (Fc) region of heavy chains contain N-glycosylation sites, where are linked structures with sialic acid residues. In this study, a capillary zone electrophoresis (CZE) method was developed and validated to quantitate DmAb and its charge variants in biopharmaceutical products. Uncoated fused-silica capillaries (50 μm i.d., 56 cm effective length) were employed, and the background electrolyte (BGE) solution was a 300 mmol/L epsilon-aminocaproic acid (EACA) and 2 mmol/L triethylenetetramine (TETA) buffer at pH 4.8 and 0.03% (v/v) Tween 20. DmAb samples were analyzed at a concentration of 5 mg/mL, spiked with the internal standard. Equally, the sialic acids levels of DmAb were determined by an reversed-phase liquid chromatography method with fluorescence detection (RP–HPLC–F), with a Kinetex® EVO C18 column (5 μm i.d., 100 Å, 250 mm × 4.6 mm). The sialic acids were released from DmAb biomolecules in a 0.5 mol/L sodium bisulfate solution (80 °C, 20 min), followed by derivatization reaction with the 40 mg/mL O-phenylenediamine (OPD) reagent (80 °C, 40 min). Besides, the in vitro bioassay was validated using RAW 264.7 macrophage cells (ATCC® TIB−71TM) that differentiated into osteoclasts. The DmAb potency were evaluated by its capacity of inhibits osteoclast cells proliferation induced in vitro. The CZE separation was obtained with a migration time approximately 11.3 min for DmAb. The CZE method demonstrated to be specific, accurate (101.61%) and robust, and were applied in conjunction with the size exclusion and reversed-phase liquid chromatographic (SE–HPLC and RP–HPLC) methods, previously validated, and with in vitro bioassay to quantitate DmAb in seven batches of Prolia®, giving mean values of content/potencies between 98.44% and 101.52%. These results were compared, demonstrating significant correlation (r > 0.98). The analytical methods enabled also to monitor charge variants, high-molecular-weight (HMW) proteins and fragments from DmAb. The RP−HPLC‒F method showed three separated peaks related to sialic acids of the DmAb biomolecule, with retention times of 9.2, 10.9, e 12.0 min. Pharmaceutical products Prolia® and Xgeva® showed 0.16 and 0.17 μg sialic acids/mg DmAb, respectively. Finally, after validation studies, the in vitro bioassay demonstrated to be specific, accurate (102.33%) and robust to evaluation of DmAb potency and were applied in conjunction with the SE–HPLC method to quantitate DmAb in six batches of Prolia®, giving mean values of content/potencies of 100.80% e 100.87%, respectively. Therefore, it is suggested that the analytical methods and the in vitro bioassay can be applied in conjunction to analyze DmAb biotechnology-derived products, establishing analytical tools that will assure the quality of the products and basis for future studies of biosimilarity of DmAb.